Religion in play: games, rituals, and virtual worlds$dreview - Wysocki, Jan (Online - Heidelberg journal of religions on the internet, 2015)
Review of Philippe Bornet
Rezension von: Bornet, Philippe, Burger, Maya (Hrsg.): Religion in play: games, rituals, and virtual worlds. - Zürich: TVZ Theologischer Verlag Zürich, 2012
Keywords: Rezension; Computerspiel; Virtuelle Realität; Ritual; Religion